Prophet Solomon Visited Many of His Wives in One Night: A Study of Thematic Hadith - Ahmad Nabil Amir; Zunaidah Mohd Marzuki (Dirasat Islamiah: Jurnal Kajian Keislaman, 2024)
The hadith about “Prophet Solomon slept with his wives (tens/hundreds) in one night” has been presented as one example of the contradiction between hadith and logic. The hadith is described as erotic and concluded as an example of forgery by hadith scholars. This study aims to clarify this accusation, examine some responses and compare ideas from important findings from Jewish and Christian sources. The research data were obtained from nine major hadith books (kutub al-tis'ah), hadith commentaries, Biblical sources, and related articles. The data were analyzed descriptively and analytically using a qualitative approach. This study found that this hadith meets the requirements of a valid hadith because it is found in hadith books and is strengthened by other valid hadiths with meaning. Thus, the accusation of forgery is completely baseless. The number of wives should be understood in general as an indication of the number of wives, not including a specific number. This hadith meaningfully indicates that it speaks of the miracles of Prophet Solomon.